Brassica juncea BRC1-1 induced by SD negatively regulates flowering by directly interacting with BjuFT and BjuFUL promoter - Feng, Junjie; Deng, Qinlin; Lu, Huanhuan; Wei, Dayong; Wang, Zhimin; Tang, Qinglin (Frontiers in Plant Science, 2022)
Flowering is crucial for sexual reproductive success in angiosperms. The core regulatory factors, such as FT, FUL, and SOC1, are responsible for promoting flowering. BRANCHED 1 (BRC1) is a TCP transcription factor gene that plays an important role in the regulation of branching and flowering in diverse plant species. However, the functions of BjuBRC1 in Brassica juncea are largely unknown. In this study, four homologs of BjuBRC1 were identified and the mechanism by which BjuBRC1 may function in the regulation of flowering time was investigated. Amino acid sequence analysis showed that BjuBRC1 contained a conserved TCP domain with two nuclear localization signals. A subcellular localization assay verified the nuclear localization of BjuBRC1. Expression analysis revealed that BjuBRC1-1 was induced by short days and was expressed abundantly in the leaf, flower, and floral bud but not in the root and stem in B. juncea. Overexpression of BjuBRC1-1 in the Arabidopsis brc1 mutant showed that BjuBRC1-1 delayed flowering time. Bimolecular fluorescent complementary and luciferase complementation assays showed that four BjuBRC1 proteins could interact with BjuFT in vivo. Notably, BjuBRC1 proteins formed heterodimers in vivo that may impact on their function of negatively regulating flowering time. Yeast one-hybrid, dual-luciferase reporter, and luciferase activity assays showed that BjuBRC1-1 could directly bind to the promoter of BjuFUL, but not BjuFT or BjuSOC1, to repress its expression. These results were supported by the reduced expression of AtFUL in transgenic Arabidopsis overexpressing BjuBRC1-1. Taken together, the results indicate that BjuBRC1 genes likely have a conserved function in the negative regulation of flowering in B. juncea.